Theoricity and Testing - Roffé, Ariel Jonathan (2023)
The observational-theoretical distinction has played a central role in the philosophy of science from logical empiricism onwards. Developments within the discipline have shown that such a distinction hides two non-identical distinctions: observational vs. non-observational and theoretical vs. non-theoretical. Likewise, metatheoretical structuralism proposed a more sophisticated treatment of theoricity in terms of the operational dependence or independence of concepts from the theories in which they appear. Despite this remarkable sophistication, it is still generally accepted that the distinction between theoretical and non-theoretical concepts coincides with the explanatory vs. non-explanatory and testing vs. non-testing distinctions. Ginnobili and Carman argued for the independence between theoricity and explanation. In this paper we will advance a claim for the independence between both theoricity and explanation, on the one hand, and testing, on the other. To do so, we propose an account of theory testing based on the framework of metatheoretical structuralism, and apply it to natural selection theory and cladistics.